Electroplating baffle for enhancing plating uniformity
Patent Information
- Application Number
- CN202610547007.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-23
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-04-23
AI Technical Summary
现有电镀挡板依然存在耐酸碱性、绝缘稳定性、耐温性较差的问题
本发明提供了一种用于增强电镀均匀性的电镀挡板,本发明通过以下方法同时提高了电镀挡板的耐酸碱性、绝缘稳定性、耐温性和电镀均匀性。
Smart Images

Figure CN122325889B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electroplating baffle technology, and more specifically to an electroplating baffle for enhancing the uniformity of electroplating. Background Technology
[0002] Ceramic substrates, with their excellent thermal conductivity, insulation properties, and high-temperature stability, have become the core substrate material for high-end electronic fields such as power semiconductors, RF modules, and high-density packaging. To meet the requirements of chip bonding, signal transmission, and long-term weather protection, a dense and uniform pure gold plating layer needs to be electroplated on the surface of the ceramic substrate. In the patterned electroplating process of ceramic substrates, the electroplating baffle is the core tooling for controlling the electric field distribution and improving the uniformity of the plating layer. However, in existing processes, electric field lines tend to concentrate at the edges and corners of the substrate, resulting in an "edge effect" where the plating layer is too thick at the edges and too thin in the center. At the same time, the large differences in the density of circuit patterns and the line width and spacing on the substrate surface can easily lead to an "pattern effect" where the current density is too high and the plating layer is too thick in fine lines and isolated pattern areas, while the plating layer is too thin in large pads and large areas of copper plating. Furthermore, traditional processes, which only adjust the main salt concentration, current density, and electroplating additives, cannot simultaneously achieve uniformity control for complex patterns and mass production, resulting in large fluctuations in product yield and failing to meet the stringent requirements of high-end packaging. Therefore, the electroplating baffle structure still needs further optimization.
[0003] In practical applications, existing electroplating baffle materials still have the following performance shortcomings: First, the substrates, such as polypropylene, have poor resistance to strong acids and strong oxidizing gold plating solutions, and are prone to swelling, degradation, and impurity precipitation with long-term use, contaminating the plating solution. Second, the substrates have insufficient insulation and dielectric stability, resulting in a decrease in the precision of electric field control after long-term use, making it impossible to maintain a stable homogenization effect. Third, they have poor temperature resistance, and are prone to warping and deformation under temperature fluctuations in the plating solution, leading to uncontrolled electric field distribution. Therefore, the acid and alkali resistance, insulation stability, and temperature resistance of existing electroplating baffle materials still need to be improved. Summary of the Invention
[0004] The purpose of this invention is to provide an electroplating baffle for enhancing electroplating uniformity, thereby solving the following technical problems: Existing electroplated baffles still suffer from poor acid and alkali resistance, insulation stability, and temperature resistance.
[0005] The objective of this invention can be achieved through the following technical solutions: An electroplating baffle for enhancing electroplating uniformity includes a baffle and baffle strips; The baffle and baffle strip are made of composite masterbatch; the composite masterbatch includes the following raw materials in parts by weight: 100-120 parts polypropylene, 15-18 parts synergistic particles, 8-10 parts hybrid crosslinking agent, 0.3-0.4 parts antioxidant, and 0.2-0.25 parts calcium stearate; The enhancing particles are polydopamine-coated and modified nano-barium titanate particles. The hybrid crosslinking agent is a dodecayl alcohol ring-opening graft modified octacyclooxycyclohexylethyl cage-type polysilsesquioxane.
[0006] Preferably, the method for preparing the synergistic particles is as follows: Nano-barium titanate was added to Tris-HCl buffer and ultrasonically dispersed at 4-10℃ for 30 min. Then, dopamine hydrochloride was added, and the mixture was stirred in an open container for 24 h. After centrifugation, washing, and drying, the synergistic particles were obtained.
[0007] Preferably, the pH of the Tris-HCl buffer is 8.5, and the total concentration of the Tris-HCl buffer pair in the Tris-HCl buffer is 10 mmol / L.
[0008] Preferably, the ratio of Tris-HCl buffer, barium titanate nanoparticles, and dopamine hydrochloride is 1500-1700 mL: 16-20 g: 1.6-2 g.
[0009] Preferably, the hybrid crosslinking agent is prepared as follows: Dodecanol and triphenylphosphine were added to octacyclohexylethyl cage-type polysilsesquioxane, and the mixture was heated to 120°C under a nitrogen atmosphere while stirring. The mixture was then stirred at 120°C for 4-5 hours. After cooling under a nitrogen atmosphere, the mixture was added to anhydrous ethanol and stirred for 30-50 minutes. The mixture was then allowed to stand for 30-60 minutes, followed by filtration, washing, and drying to obtain the hybrid crosslinking agent.
[0010] Preferably, the ratio of the octacyclohexylethyl cage-type polysilsesquioxane, dodecanol, triphenylphosphine, and anhydrous ethanol is 50g:20.96g:0.5g:500-550mL.
[0011] Preferably, the baffle and baffle strip are prepared by the following method: S1: Polypropylene, synergistic particles, hybrid crosslinking agent, antioxidant, and calcium stearate are mixed at 1500 r / min for 5-10 min. Then, the mixture is melt-extruded using a co-rotating parallel twin-screw extruder (length-to-diameter ratio 40:1, standard vacuum exhaust system, screw assembly includes 2 sets of high-shear compound blocks). After water cooling, pelletizing, and drying at 80℃ for 4-6 h, the composite masterbatch is obtained. S2: The composite masterbatch is injection molded and demolded, then annealed at 80℃ for 2 hours, and after cooling, 2mm thick baffles and baffles are obtained.
[0012] Preferably, in the melt extrusion process described in S1, the feed section is 180°C, the melting section is 200°C, the mixing section is 210°C, the venting section is 200°C, the die head section is 195°C, the screw speed is 300 r / min, the feeding rate is 10 kg / h, and the vacuum venting degree is -0.08 MPa.
[0013] Preferably, during the injection molding process described in S2, the temperature of the barrel feed section is 190°C, the middle section is 200°C, the discharge section is 210°C, the nozzle is 210°C, the temperature of the baffle and baffle mold is 60°C, the injection pressure is 80MPa, the holding pressure is 60MPa, the holding time is 8s, and the cooling time is 30s.
[0014] Preferably, the baffle includes an outer region and an inner region, wherein the outer region is a plate with through holes and the inner region is hollow; The outer layer of the baffle is provided with a fixing clip to facilitate the insertion and removal of the baffle strip; The outer layer of the baffle has nine slots. The baffle is either a fully filled baffle or a baffle with a through hole; The through hole on the baffle is the same size as the through hole in the outer layer of the baffle. When the baffle is matched with the baffle, the through hole of the baffle can coincide with the through hole of the baffle.
[0015] The beneficial effects of this invention are: This invention provides an electroplating baffle for enhancing electroplating uniformity. The invention improves the acid and alkali resistance, insulation stability, temperature resistance, and electroplating uniformity of the electroplating baffle simultaneously through the following methods.
[0016] (1) In the enhanced particles of the present invention, the polydopamine coating layer can slow down the corrosion of barium titanate core by acid and alkali media; its surface active groups such as catechol and amino groups can form stable chemical bonds with hybrid crosslinking agents, seal the interfacial pores between the filler and the polypropylene matrix, block the acid and alkali penetration channels, inhibit the swelling and degradation of the polypropylene matrix, reduce the mass change rate after long-term acid and alkali immersion, reduce filler precipitation and matrix corrosion, and improve acid and alkali resistance stability. Although the intrinsic insulation performance of barium titanate is lower than that of polypropylene, polydopamine coating can significantly improve the dispersibility of nanoparticles, avoid the formation of conductive paths by powder agglomeration and increase dielectric loss; strong interfacial bonding can suppress interfacial air gap defects, prevent insulation failure caused by filler dissolution after long-term immersion, so that the composite material maintains a high volume resistivity close to that of pure polypropylene, greatly improves the insulation performance retention rate after chemical immersion, stabilizes dielectric parameters, and avoids the decay of electric field control precision. High-melting-point barium titanate rigid particles can restrict the high-temperature movement of polypropylene molecular chains; uniformly dispersed core-shell particles can form a thermal barrier network, and the chemical bonding between polydopamine and hybrid crosslinking agents can form rigid nodes, inhibiting high-temperature slippage of molecular chains, increasing the material's load deformation temperature, reducing the high-temperature dimensional change rate, and improving thermal stability and creep resistance. High-dielectric-constant barium titanate can impart electric field homogenization capabilities to the composite material, refracting and redistributing electric field lines passing through the baffle, significantly mitigating electroplating edge effects and pattern effects; uniformly dispersed particles ensure uniform dielectric properties across the entire domain, avoiding local electric field distortion; stable material properties ensure that the long-term electric field control capability does not decay, significantly reducing the relative standard deviation of gold plating thickness, greatly improving electroplating uniformity, and alleviating the industry pain point of excessively thick edge plating and thin center plating.
[0017] (2) The hybrid crosslinking agent of the present invention is a polyepoxy-based cage-type polysilsesquioxane obtained by ring-opening grafting modification of octaepoxycyclohexylethyl cage-type polysilsesquioxane with dodecyl alcohol in a set ratio. Among them, the long-chain modification of dodecyl alcohol can significantly improve the compatibility between the modified epoxy cage-type polysilsesquioxane and the polypropylene matrix, and avoid the permeation pores caused by phase separation; its cage-type Si-O-Si inorganic skeleton has excellent intrinsic chemical corrosion resistance and can form a dense molecular barrier; the remaining epoxy groups can chemically bond with the polydopamine on the surface of the synergistic particles, and at the same time, the modified epoxy cage-type polysilsesquioxane can ring-open self-polymerize to form a local chemical crosslinking structure. Combined with the strong physical entanglement formed by the long chain of dodecyl alcohol and the polypropylene molecular chain, a three-dimensional physical-chemical hybrid network is constructed together, which closes the gaps between molecular chains, inhibits the swelling of the matrix and the precipitation of small molecules, significantly improves the resistance to strong acids, strong alkalis and organic solvents, reduces the quality change rate after long-term immersion, and reduces the risk of plating solution pollution. The cage-like structure of modified epoxy-cage polysilsesquioxane inherently exhibits low dielectric loss and high insulation. Its three-dimensional physical-chemical hybrid network reduces the free volume and structural defects of the polypropylene matrix, suppressing carrier migration. The homogeneous compatibility system avoids insulation defects caused by phase separation during long-term use, stabilizing dielectric properties and thus maintaining excellent initial insulation performance of the composite material. It also improves insulation stability after damp heat and chemical aging, and maintains the long-term precision of the baffle's electric field control. The Si-O-Si inorganic skeleton of the modified epoxy-cage polysilsesquioxane exhibits significantly better heat resistance than organic polymers, substantially increasing the material's thermal decomposition temperature. The physical entanglement and local cross-linking network rigidly constrain the high-temperature slippage and creep of the polypropylene molecular chains. Strong interfacial bonding efficiently transfers thermal stress, reduces high-temperature warpage deformation, significantly increases the load deformation temperature, reduces the high-temperature dimensional change rate, and ensures the dimensional accuracy of the baffle during long-term use. The cross-linked network and high heat resistance ensure the dimensional stability of the baffle during long-term use, preventing uncontrolled electric field distribution caused by warping deformation. Stable insulation and dielectric properties ensure batch consistency in electric field homogenization. The uniform matrix structure avoids electric field distortion caused by local dielectric fluctuations, forming a synergistic effect of dielectric regulation with the synergistic particles, ensuring long-term batch stability of electroplating uniformity, further reducing the relative standard deviation of coating thickness, and meeting the stringent requirements of batch electroplating of ceramic substrates. The core-shell structure of the synergistic particles can form interfacial chemical bonds with the hybrid cross-linking agent, solving the compatibility problem between inorganic fillers and polypropylene matrix, and constructing a multi-level structure of "rigid ceramic particles - cage-type cross-linking nodes - polymer matrix", synergistically achieving a simultaneous leap in corrosion resistance, insulation, temperature resistance, and electric field regulation performance.
[0018] (3) In the structural design of the electroplating baffle of the present invention, the outer layer is fully filled with a through-hole area to form a controllable electric field shielding layer, which physically constrains the electric field lines diverging from the cathode edge, forcing the electric field lines to pass through only through the preset through-holes, and suppressing the concentration of electric field lines at the edge; the hollow area of the inner layer is adapted to the cathode core coating area, avoiding excessive shielding of the electric field in the central area, balancing the electric field flux at the edge and the center, greatly weakening the electroplating edge effect, significantly reducing the coating thickness difference between the substrate edge and the central area, and improving the uniformity of the coating across the entire substrate. The array of through-holes with equal aperture and spacing constrains and redirects the electric field lines passing through the baffle, making the originally disordered and distorted spatial electric field distribution tend to be uniform; the fixed aperture and spacing can precisely control the electric field flux and distribution density, and combined with the dielectric homogenization characteristics of the composite substrate, form a dual homogenization effect of physical on / off and dielectric control, eliminating local electric field distortion, stabilizing the current density distribution on the cathode surface, and significantly reducing the relative standard deviation of the coating thickness. Nine standardized slots, paired with two types of baffles—fully filled and with through holes—allow for flexible adjustment of the baffle opening ratio, opening position, and shading area. Precise customization of the electric field distribution can be achieved without replacing the baffle itself. For fine lines and isolated graphic areas with high current density, the corresponding through holes can be closed to reduce the electric field flux and lower the local current density. For large pads and large copper-clad areas with low current density, the through holes can be retained to supplement the electric field flux, increase the local current density, and precisely counteract graphic effects. This allows for precise adaptation to the electroplating requirements of complex patterned ceramic substrates, significantly alleviating the problem of uneven plating thickness caused by graphic effects, while ensuring the consistency of plating uniformity between different product specifications and batches. This structural design forms a strong synergy with the material system: the material system ensures the intrinsic ability and long-term stability of electric field homogenization, while the structural design enables precise, flexible, and customizable control of the electric field distribution. The combination of the two can simultaneously suppress edge effects and graphic effects.
[0019] Of course, any product implementing this invention does not necessarily need to achieve all of the advantages described above at the same time. Attached Figure Description
[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1 This is a schematic diagram of the structure of the electroplating baffle prepared according to an embodiment of the present invention for enhancing electroplating uniformity. Detailed Implementation
[0022] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0023] In the description of this invention, it should be understood that the terms "opening", "upper", "lower", "thickness", "top", "middle", "length", "inner", "around", etc., which indicate orientation or positional relationship, are only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the components or elements referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as limiting this invention.
[0024] Unless otherwise specified, the following information pertains to some of the raw materials used in the following embodiments and comparative examples of this invention: Octacyclohexylethyl cage-type polysilsesquioxane was purchased from Xi'an Qiyue Biotechnology Co., Ltd.; polypropylene (melt index 4g / 10min, isotacticity ≥96%) was purchased from Shanghai Mairui Biochemical Technology Co., Ltd., item number: M86998.
[0025] Example 1: A method for preparing an electroplating baffle to enhance electroplating uniformity is as follows: S1: 16g of barium titanate nanoparticles (particle size 200nm) were added to 1500mL of Tris-HCl buffer with a total concentration of 10mmol / L and pH of 8.5 and ultrasonically dispersed at 4℃ for 30min. Then, 1.6g of dopamine hydrochloride was added, and the mixture was stirred in an open container for 24h before centrifugation. The precipitate was then washed three times with deionized water and once with anhydrous ethanol. Finally, it was vacuum dried at 50℃ for 24h to obtain the synergistic particles. S2: 20.96g dodecanol and 0.5g triphenylphosphine were added to 50g octacyclohexylethyl cage-type polysilsesquioxane and heated to 120℃ under nitrogen atmosphere while stirring. The mixture was then stirred at 120℃ for 4h. After cooling under nitrogen atmosphere, the mixture was added to 500mL anhydrous ethanol and stirred for 30min. The mixture was then allowed to stand for 30min, filtered, and the precipitate was washed three times with anhydrous ethanol. Finally, the mixture was vacuum dried at 60℃ for 12h to obtain the hybrid crosslinking agent. S3: Mix 100g polypropylene, 15g synergistic granules, 8g hybrid crosslinking agent, 0.2g antioxidant 1010, 0.1g antioxidant 168, and 0.2g calcium stearate at 1500r / min for 5min. Then, use a co-rotating parallel twin-screw extruder (length-to-diameter ratio 40:1, standard vacuum exhaust system, screw assembly includes 2 sets of high-shear compound blocks) for melt extrusion at 180℃ in the feeding section, 200℃ in the melting section, 210℃ in the mixing section, 200℃ in the exhaust section, 195℃ in the die head section, screw speed 300r / min, feed rate 10kg / h, and vacuum exhaust degree -0.08MPa. After that, water cool, pelletize, and dry at 80℃ for 4h to obtain composite masterbatch. S4: The composite masterbatch is injection molded with the following temperature settings: feed section temperature 190℃, middle section temperature 200℃, discharge section temperature 210℃, nozzle temperature 210℃, baffle and baffle mold temperature 60℃, injection pressure 80MPa, holding pressure 60MPa, holding time 8s, and cooling time 30s. After demolding, it is then annealed at 80℃ for 2 hours. After cooling, 2mm thick baffles and baffles are obtained.
[0026] S5: Electroplating baffles are prepared using baffles and baffles to enhance the uniformity of electroplating.
[0027] Appendix Figure 1 The diagram shows a schematic representation of an electroplating baffle used to enhance electroplating uniformity according to an embodiment of the present invention. The baffle 100 includes an outer region and an inner region. The outer region is a main body plate with through holes, and the inner region is hollow. The shaded area of the outer region of the baffle 100 is a plate made of composite masterbatch. The circular holes 110 on the outer region of the baffle 100 are hollow channels that allow the solution and electric field lines to pass through, while also redistributing the distribution of the electric field lines. The inner region 111 of the baffle 100 is hollow. The area; the fixing clip 121 on the outer area of the baffle 100 has a fixing function for the baffle strip, which facilitates the insertion and removal of the baffle strip; the nine slots 131-139 on the outer area of the baffle 100 can be matched with the corresponding baffle strip during use; the baffle strip 200 is a fully filled baffle strip; the baffle strip 300 is a baffle strip with a through hole; the round hole 310 on the baffle strip 300 is a hollow channel with the same size as the round hole 110. When the baffle strip 300 is matched with the baffle 100, the through hole 310 of the baffle strip and the through hole 110 of the baffle strip can coincide.
[0028] In use, the electroplating baffle is fixed in the plating tank between the anode and cathode, at a distance of 8cm from the cathode. The lower end of the baffle contacts the bottom of the tank, and the upper end of the baffle is above the liquid surface. The baffle is placed vertically, with one baffle on each side of the cathode. The baffle opening diameter is 2cm, the horizontal spacing between the holes is 9cm, and at least four through holes are provided in the vertical direction. For any extra holes, baffle strips 200 or 300 can be used to cover them. The number of openings in the baffle strips can be less than the number of openings in a single slot of the baffle, thus adjusting the covering area of a single slot. The fixing clips on both sides of the slot can fix the baffle strips to the corresponding positions on the baffle, and insertion and removal are simple, facilitating the adjustment of the covering position.
[0029] Example 2: A method for preparing an electroplating baffle to enhance electroplating uniformity is as follows: S1: 18g of barium titanate nanoparticles (particle size 200nm) were added to 1600mL of Tris-HCl buffer with a total concentration of 10mmol / L and pH of 8.5 and ultrasonically dispersed at 8℃ for 30min. Then, 1.8g of dopamine hydrochloride was added, and the mixture was stirred in an open container for 24h before centrifugation. The precipitate was then washed 4 times with deionized water and 2 times with anhydrous ethanol. Finally, it was vacuum dried at 50℃ for 24h to obtain the synergistic particles. S2: 20.96g dodecanol and 0.5g triphenylphosphine were added to 50g octacyclohexylethyl cage-type polysilsesquioxane and heated to 120℃ under nitrogen atmosphere while stirring. The mixture was then stirred at 120℃ for 4.5h. After cooling under nitrogen atmosphere, the mixture was added to 530mL anhydrous ethanol and stirred for 40min. The mixture was then allowed to stand for 40min, filtered, and the precipitate was washed 4 times with anhydrous ethanol. Finally, the mixture was vacuum dried at 60℃ for 12h to obtain the hybrid crosslinking agent. S3: Mix 110g polypropylene, 16.5g synergistic granules, 9g hybrid crosslinking agent, 0.23g antioxidant 1010, 0.13g antioxidant 168, and 0.23g calcium stearate at 1500r / min for 8min. Then, use a co-rotating parallel twin-screw extruder (length-to-diameter ratio 40:1, standard vacuum exhaust system, screw assembly includes 2 sets of high-shear compound blocks) for melt extrusion at 180℃ in the feeding section, 200℃ in the melting section, 210℃ in the mixing section, 200℃ in the exhaust section, 195℃ in the die head section, screw speed 300r / min, feed rate 10kg / h, and vacuum exhaust degree -0.08MPa. After that, water cool, pelletize, and dry at 80℃ for 5h to obtain composite masterbatch. S4: The composite masterbatch is injection molded with the following temperature settings: feed section temperature 190℃, middle section temperature 200℃, discharge section temperature 210℃, nozzle temperature 210℃, baffle and baffle mold temperature 60℃, injection pressure 80MPa, holding pressure 60MPa, holding time 8s, and cooling time 30s. After demolding, it is then annealed at 80℃ for 2 hours. After cooling, 2mm thick baffles and baffles are obtained.
[0030] S5: Electroplating baffles are prepared using baffles and baffles to enhance the uniformity of electroplating.
[0031] Appendix Figure 1 The diagram shows a schematic representation of an electroplating baffle used to enhance electroplating uniformity according to an embodiment of the present invention. The baffle 100 includes an outer region and an inner region. The outer region is a main body plate with through holes, and the inner region is hollow. The shaded area of the outer region of the baffle 100 is a plate made of composite masterbatch. The circular holes 110 on the outer region of the baffle 100 are hollow channels that allow the solution and electric field lines to pass through, while also redistributing the distribution of the electric field lines. The inner region 111 of the baffle 100 is hollow. The area; the fixing clip 121 on the outer area of the baffle 100 has a fixing function for the baffle strip, which facilitates the insertion and removal of the baffle strip; the nine slots 131-139 on the outer area of the baffle 100 can be matched with the corresponding baffle strip during use; the baffle strip 200 is a fully filled baffle strip; the baffle strip 300 is a baffle strip with a through hole; the round hole 310 on the baffle strip 300 is a hollow channel with the same size as the round hole 110. When the baffle strip 300 is matched with the baffle 100, the through hole 310 of the baffle strip and the through hole 110 of the baffle strip can coincide.
[0032] In use, the electroplating baffle is fixed in the plating tank between the anode and cathode, at a distance of 8cm from the cathode. The lower end of the baffle contacts the bottom of the tank, and the upper end of the baffle is above the liquid surface. The baffle is placed vertically, with one baffle on each side of the cathode. The baffle opening diameter is 2cm, the horizontal spacing between the holes is 9cm, and at least four through holes are provided in the vertical direction. For any extra holes, baffle strips 200 or 300 can be used to cover them. The number of openings in the baffle strips can be less than the number of openings in a single slot of the baffle, thus adjusting the covering area of a single slot. The fixing clips on both sides of the slot can fix the baffle strips to the corresponding positions on the baffle, and insertion and removal are simple, facilitating the adjustment of the covering position.
[0033] Example 3: A method for preparing an electroplating baffle to enhance electroplating uniformity is as follows: S1: 20g of barium titanate nanoparticles (particle size 200nm) were added to 1700mL of Tris-HCl buffer with a total concentration of 10mmol / L and pH of 8.5 and ultrasonically dispersed at 10℃ for 30min. Then, 2g of dopamine hydrochloride was added, and the mixture was stirred in an open container for 24h before centrifugation. The precipitate was then washed 5 times with deionized water and 3 times with anhydrous ethanol. Finally, it was vacuum dried at 50℃ for 24h to obtain the synergistic particles. S2: 20.96g dodecanol and 0.5g triphenylphosphine were added to 50g octacyclohexylethyl cage-type polysilsesquioxane and heated to 120℃ under nitrogen atmosphere while stirring. The mixture was then stirred at 120℃ for 5h. After cooling under nitrogen atmosphere, the mixture was added to 550mL anhydrous ethanol and stirred for 50min. The mixture was then allowed to stand for 60min, filtered, and the precipitate was washed 5 times with anhydrous ethanol. Finally, the mixture was vacuum dried at 60℃ for 12h to obtain the hybrid crosslinking agent. S3: Mix 120g polypropylene, 18g synergistic granules, 10g hybrid crosslinking agent, 0.25g antioxidant 1010, 0.15g antioxidant 168, and 0.25g calcium stearate at 1500r / min for 10min. Then, use a co-rotating parallel twin-screw extruder (length-to-diameter ratio 40:1, standard vacuum exhaust system, screw assembly includes 2 sets of high-shear compound blocks) for melt extrusion at 180℃ in the feeding section, 200℃ in the melting section, 210℃ in the mixing section, 200℃ in the exhaust section, 195℃ in the die head section, screw speed 300r / min, feed rate 10kg / h, and vacuum exhaust degree -0.08MPa. After that, water cool, pelletize, and dry at 80℃ for 6h to obtain composite masterbatch. S4: The composite masterbatch is injection molded with the following temperature settings: feed section temperature 190℃, middle section temperature 200℃, discharge section temperature 210℃, nozzle temperature 210℃, baffle and baffle mold temperature 60℃, injection pressure 80MPa, holding pressure 60MPa, holding time 8s, and cooling time 30s. After demolding, it is then annealed at 80℃ for 2 hours. After cooling, 2mm thick baffles and baffles are obtained.
[0034] S5: Electroplating baffles are prepared using baffles and baffles to enhance the uniformity of electroplating.
[0035] Appendix Figure 1The diagram shows a schematic representation of an electroplating baffle used to enhance electroplating uniformity according to an embodiment of the present invention. The baffle 100 includes an outer region and an inner region. The outer region is a main body plate with through holes, and the inner region is hollow. The shaded area of the outer region of the baffle 100 is a plate made of composite masterbatch. The circular holes 110 on the outer region of the baffle 100 are hollow channels that allow the solution and electric field lines to pass through, while also redistributing the distribution of the electric field lines. The inner region 111 of the baffle 100 is hollow. The area; the fixing clip 121 on the outer area of the baffle 100 has a fixing function for the baffle strip, which facilitates the insertion and removal of the baffle strip; the nine slots 131-139 on the outer area of the baffle 100 can be matched with the corresponding baffle strip during use; the baffle strip 200 is a fully filled baffle strip; the baffle strip 300 is a baffle strip with a through hole; the round hole 310 on the baffle strip 300 is a hollow channel with the same size as the round hole 110. When the baffle strip 300 is matched with the baffle 100, the through hole 310 of the baffle strip and the through hole 110 of the baffle strip can coincide.
[0036] In use, the electroplating baffle is fixed in the plating tank between the anode and cathode, at a distance of 8cm from the cathode. The lower end of the baffle contacts the bottom of the tank, and the upper end of the baffle is above the liquid surface. The baffle is placed vertically, with one baffle on each side of the cathode. The baffle opening diameter is 2cm, the horizontal spacing between the holes is 9cm, and at least four through holes are provided in the vertical direction. For any extra holes, baffle strips 200 or 300 can be used to cover them. The number of openings in the baffle strips can be less than the number of openings in a single slot of the baffle, thus adjusting the covering area of a single slot. The fixing clips on both sides of the slot can fix the baffle strips to the corresponding positions on the baffle, and insertion and removal are simple, facilitating the adjustment of the covering position.
[0037] Comparative Example 1: Compared with Example 1, this comparative example only replaces the "enhancing particles" added in the preparation process of S3 with "nano barium titanate". All other steps and parameters are the same, and will not be repeated in this comparative example. Finally, an electroplating baffle is obtained to enhance the uniformity of electroplating.
[0038] Comparative Example 2: Compared with Example 1, this comparative example only did not add "enhancing particles" in the preparation process of S3. All other steps and parameters were the same, and will not be repeated here. The final result is an electroplating baffle used to enhance the uniformity of electroplating.
[0039] Comparative Example 3: Compared with Example 1, this comparative example only replaces the "hybrid crosslinking agent" added during the preparation of S3 with "octacyclooxycyclohexylethyl cage-type polysilsesquioxane". All other steps and parameters are the same, and will not be repeated in this comparative example. Finally, an electroplating baffle is obtained to enhance the uniformity of electroplating.
[0040] Comparative Example 4: Compared with Example 1, this comparative example only did not add a "hybrid crosslinking agent" in the preparation process of S3. All other steps and parameters were the same, and will not be repeated here. The final result is an electroplating baffle used to enhance the uniformity of electroplating.
[0041] Comparative Example 5: Compared with Example 1, this comparative example only omits the addition of "enhancing particles and hybrid crosslinking agent" in the preparation process of S3. All other steps and parameters are the same, and will not be repeated here. The final result is an electroplating baffle used to enhance the uniformity of electroplating.
[0042] Performance testing: Determination of acid and alkali resistance: Referring to GB / T 11547-2008 standard, the composite masterbatches prepared in Examples 1-3 and Comparative Examples 1-5 of this invention were made into 80mm×10mm×4mm samples according to the method in S4. The samples were tested at 60℃ in the following conditions: ① Gold plating working solution (30g citric acid monohydrate, 120g potassium citrate trihydrate, 20g potassium sulfate, and 0.5g disodium EDTA were added sequentially to 800mL deionized water, stirred until dissolved, then 2.93g potassium gold cyanide was added, stirred until dissolved, and then 10% citric acid was added). The following steps were performed: ① pH adjustment to 4.2 with a solution of potassium hydroxide / hydrochloric acid, followed by final volume adjustment to 1L with deionized water; ② oil removal solution (15g anhydrous sodium carbonate and 30g trisodium phosphate dodecahydrate were added to 800mL of deionized water, stirred to dissolve, then 25g sodium hydroxide was added, followed by pH adjustment to 12.5 with a 10% sodium hydroxide / hydrochloric acid solution, followed by final volume adjustment to 1L with deionized water); ③ mass change rate (%) after soaking in a 50% nitric acid aqueous solution for 720h. The results are shown in Table 1.
[0043] Determination of insulation stability: Referring to GB / T 1410-2006 standard, the volume resistivity of the composite masterbatches prepared in Examples 1-3 and Comparative Examples 1-5 of this invention, and the samples (80mm×10mm×4mm) prepared according to the method in S4, were tested before and after immersion in the gold plating working solution at 60℃ for 720h, under the conditions of 23℃ and 50% relative humidity. The volume resistivity retention rate (%) after immersion was calculated, and the results are shown in Table 1.
[0044] Temperature resistance determination: Referring to GB / T 1634.2-2019 standard, the composite masterbatches prepared in Examples 1-3 and Comparative Examples 1-5 of this invention were used to prepare samples (80mm×10mm×4mm) according to the method in S4. The temperature (°C) at which the deformation amount of 0.34mm was measured under a bending load of 0.45MPa at a heating rate of 2°C / min. The measurement results are shown in Table 1.
[0045] Determination of electroplating uniformity: The electroplating baffles for enhancing electroplating uniformity, prepared according to Examples 1-3 and Comparative Examples 1-5 of this invention, were fixed between the anode and cathode of an acidic gold plating tank, placed vertically 8 cm away from the cathode, with one baffle on each side of the cathode. The lower end of the baffle was in contact with the bottom of the tank, and the upper end was above the surface of the plating solution. Pure gold electroplating of ceramic substrates was performed using process parameters consistent with actual mass production: the substrate was a 96% alumina ceramic substrate (with a patterned nickel-gold underlayer on the surface, containing standard test patterns covering the four corners, four sides, and central area of the substrate, as well as 10μm / 10μm linewidth and spacing patterns, isolated pads, and a large 20mm×20mm copper-clad area); the plating solution was ① gold plating working solution, the plating solution temperature was 60℃, and the current density was 0.5A / dm³. 2 The electroplating time was 10 minutes. Then, the thickness of the pure gold plating was measured at 15 test points (completely covering the center of the substrate, the midpoint of the four sides, the four corners, and the different feature areas), and the relative standard deviation of the pure gold plating thickness RSD (%, plating thickness standard deviation SD / plating thickness arithmetic mean × 100%) was calculated. The measurement results are shown in Table 1.
[0046] Table 1: Performance test results of Examples 1-3 and Comparative Examples 1-5
[0047] Data Analysis: As can be seen from Table 1, the electroplating baffle prepared in the embodiments of the present invention for enhancing electroplating uniformity also has excellent acid and alkali resistance, insulation stability, temperature resistance and electroplating uniformity.
[0048] The foregoing has provided a detailed description of one embodiment of the present invention, but this description is merely a preferred embodiment and should not be construed as limiting the scope of the invention. All equivalent variations and modifications made within the scope of the claims of this invention should still fall within the patent coverage of this invention.
Claims
1. An electroplating baffle for enhancing electroplating uniformity, characterized in that, Including baffles and baffle strips; The baffle and baffle strip are made of composite masterbatch; the composite masterbatch includes the following raw materials in parts by weight: 100-120 parts polypropylene, 15-18 parts synergistic particles, 8-10 parts hybrid crosslinking agent, 0.3-0.4 parts antioxidant, and 0.2-0.25 parts calcium stearate; The enhancing particles are polydopamine-coated and modified nano-barium titanate particles. The preparation method of the hybrid crosslinking agent is as follows: dodecanol and triphenylphosphine are added to octacyclohexylethyl cage-type polysilsesquioxane and heated to 120°C under nitrogen atmosphere while stirring. Then, the mixture is stirred at 120°C for 4-5 hours. After cooling under nitrogen atmosphere, it is added to anhydrous ethanol and stirred for 30-50 minutes. Then, it is allowed to stand for 30-60 minutes, followed by filtration, washing, and drying to obtain the hybrid crosslinking agent.
2. The electroplating baffle for enhancing electroplating uniformity according to claim 1, characterized in that, The preparation method of the synergistic granules is as follows: Barium titanate nanoparticles were added to Tris-HCl buffer and ultrasonically dispersed at 4-10℃ for 30 min. Then, dopamine hydrochloride was added, and the mixture was stirred for 24 h. After centrifugation, washing, and drying, the enhanced particles were obtained.
3. The electroplating baffle for enhancing electroplating uniformity according to claim 2, characterized in that, The pH of the Tris-HCl buffer is 8.5, and the total concentration of the Tris-HCl buffer pair in the Tris-HCl buffer is 10 mmol / L.
4. The electroplating baffle for enhancing electroplating uniformity according to claim 2, characterized in that, The ratio of Tris-HCl buffer, barium titanate nanoparticles, and dopamine hydrochloride is 1500-1700 mL: 16-20 g: 1.6-2 g.
5. The electroplating baffle for enhancing electroplating uniformity according to claim 1, characterized in that, The ratio of the amount of the octacyclohexylethyl cage-type polysilsesquioxane, dodecanol, triphenylphosphine, and anhydrous ethanol is 50g:20.96g:0.5g:500-550mL.
6. The electroplating baffle for enhancing electroplating uniformity according to claim 1, characterized in that, The preparation methods of the baffle and baffle strip are as follows: S1: Mix polypropylene, synergistic particles, hybrid crosslinking agent, antioxidant, and calcium stearate at 1500 r / min for 5-10 min, then perform melt extrusion treatment, followed by water cooling, pelletizing, and drying to obtain composite masterbatch. S2: The composite masterbatch is injection molded and demolded, then annealed at 80℃ for 2 hours, and after cooling, baffles and baffle strips are obtained.
7. The electroplating baffle for enhancing electroplating uniformity according to claim 6, characterized in that, In the melt extrusion process described in S1, the extruder feed section is 180°C, the melting section is 200°C, the mixing section is 210°C, the venting section is 200°C, the die head section is 195°C, the screw speed is 300 r / min, the feeding rate is 10 kg / h, and the vacuum venting degree is -0.08 MPa.
8. The electroplating baffle for enhancing electroplating uniformity according to claim 6, characterized in that, In the injection molding process described in S2, the temperature of the barrel feed section is 190℃, the middle section is 200℃, the discharge section is 210℃, the nozzle is 210℃, the temperature of the baffle and baffle mold is 60℃, the injection pressure is 80MPa, the holding pressure is 60MPa, the holding time is 8s, and the cooling time is 30s.
9. The electroplating baffle for enhancing electroplating uniformity according to claim 1, characterized in that, The baffle includes an outer region and an inner region. The outer region is a plate with through holes, and the inner region is hollow. The outer layer of the baffle is provided with a fixing clip and 9 clip slots; The stop bar can be either a fully filled stop bar or a stop bar with a through hole.
Citation Information
Patent Citations
High-dielectric-constant polypropylene composite material and preparation method thereof
CN111961283A
Melt processable thermoplastic composite comprising a multimodal dielectric filler
US20190291364A1